Memory stem CD8+T cells in HIV/Mtb mono- and co-infection: characteristics, implications, and clinical significance - Xiao, Jing; Wang, Fuchun; Yan, Hongxia; Wang, Bo; Su, Bin; Lu, Xiaofan; Zhang, Tong (Frontiers in Cellular and Infection Microbiology, 2024)
Human immunodeficiency Virus (HIV) and Mycobacterium tuberculosis (Mtb) co-infection presents a significant public health challenge worldwide. Comprehensive assessment of the immune response in HIV/Mtb co-infection is complex and challenging. CD8+T cells play a pivotal role in the adaptive immune response to both HIV and Mtb. The differentiation of CD8+T cells follow a hierarchical pattern, with varying degrees of exhaustion throughout the process. Memory stem T cells (TSCM cells) is at the apex of the memory T lymphocyte system, which has recently emerged as a promising target in immunotherapy. In this context, we discuss the alterations of CD8+TSCM cells in HIV/Mtb mono- and co-infection, their implications and clinical significance, and potential for improving immunotherapy.